COPD phenotypes in a lung cancer screening population. (28th July 2014) - Balkan, Arzu; Bulut, Yonca; Fuhrman, Carl R.; Fisher, Stephen N.; Wilson, David O.; Weissfeld, Joel L.; Sciurba, Frank C.
Abstract: Background and Aims: COPD (chronic obstructive pulmonary disease) is a very heterogeneous disease, and phenotypic categorization of a high‐risk population has many potential benefits. The present study uses a symptom questionnaire, low‐dose computed tomography (LDCT) and pulmonary function tests (PFT) to phenotypically subgroup a high‐risk population. Methods: Study group consisted of current or former smokers who underwent lung cancer screening with LDCT as a subgroup of Pittsburgh Lung Screening Study. In addition to LDCT, PFT and a symptom query questionnaire were obtained from each patient. Results: The study group consisted of 3183 subjects (age 50–79) subdivided into eight groups according to presence of symptoms, obstruction on PFT and presence of emphysema on LDCT. A total of 501 (15.7%) subjects were asymptomatic, with no airflow obstruction or evidence of emphysema. There were 866 (27.2%) subjects with both obstruction on PFT and emphysema on LDCT, but only 660 (20.7%) had symptoms. Five hundred thirty (16.6%) of the subjects had no emphysema on LDCT but had obstruction on PFT, although only 370 (11.6%) had symptoms. Four hundred seventy‐four (14.9%) of subjects had emphysema on LDCT, but no airflow obstruction, with 312 (9.8%) symptomatic. Finally, 812 (25.5%) of subjects had no evidence of airflow obstruction on PFT or emphysema on LDCT, but had symptoms. Conclusion: Combining LDCT with PFT and a comprehensive questionnaire allows subgroup classification of COPD phenotypes in a high‐risk population and may lead to earlier intervention and an improved framework for future studies.